Bạn tự vẽ hình nhé!
Ta có: \(\Delta OA'B'\sim\Delta OAB\left(g\cdot g\right)\)
\(\Rightarrow\dfrac{OA'}{OA}=\dfrac{A'B'}{AB}\left(1\right)\)
Ta có: \(\Delta F'A'B'\sim\Delta F'OI\left(g\cdot g\right)\)
\(\Rightarrow\dfrac{F'A'}{F'O}=\dfrac{A'B'}{OI}\)
Mà \(OI=AB\)
\(\Rightarrow\dfrac{F'A'}{F'O'}=\dfrac{A'B'}{AB}\left(2\right)\)
Từ (1) và (2) \(\Rightarrow\dfrac{OA'}{OA}=\dfrac{F'A'}{F'O}=\dfrac{OA'-OF'}{OF'}\)
\(\Leftrightarrow\dfrac{OA'}{7}=\dfrac{OA'-4}{4}\)
\(\Leftrightarrow4OA'=\left(OA'-4\right)\cdot7\)
\(\Leftrightarrow-3OA'=-28\)
\(\Leftrightarrow OA'=\dfrac{28}{3}\left(cm\right)\)
Thay vào (1): \(\dfrac{\dfrac{28}{3}}{7}=\dfrac{A'B'}{2}\)
\(\Rightarrow A'B'=\dfrac{8}{3}\left(cm\right)\)
Vậy chiều cao của ảnh là \(\dfrac{8}{3}\left(cm\right)\)